Interplay of aurora kinase a functional residues and Epstein-barr Nuclear Antigen 1 in Epstein-barr virus associated Gastric cancer using AGS cells - Nidhi Varshney; Siddharth Singh; Meenakshi Kandpal; Vaishali Saini; Erle S. Roberston; Hem Chandra Jha (BMC Cancer)
Abstract Epstein-Barr virus (EBV), an oncogenic gamma-herpesvirus, belongs to group 1 carcinogen and is implicated in various cancers, including gastric cancer. Aurora Kinase A is a major mitotic protein kinase that regulates mitotic progression; overexpression and hyperactivation of AURKA commonly promote genomic instability in many tumours. However, the relationship of functional residues of AURKA and EBV in gastric cancer progression remains unknown. We reveal that AURKA overexpression and EBV infection induce aneuploidy in gastric epithelial cells. The AURKA (S89) N-terminal residue is critical for the centrosome maturation process in EBV-infected gastric epithelial cells. The kinase domain residues T287 and T288 of AURKA are essential for centrosome maturation and bipolar spindle formation in EBV-infected gastric cancer cells. We also show that AURKA 287/288 dm reduces the transcript expression of cell cycle markers involved in mitotic entry in EBV infection. This mutant also enhanced the protein expression of p53 and Rb, which was reduced in EBV infection and decreased the Survivin expression. Further, EBNA1, the latent gene of EBV, stabilises the AURKA in its wild-type form and S89A mutant but unable to stabilise in T287/288A double mutant. These mutants also induce mitotic catastrophe by regulating the apoptosis and autophagy pathway in EBV infection. AURKA287/288 dm also promotes autophagosome formation even in EBV infection. Thus, this study demonstrates that the AURKA kinase domain is essential for its functioning and progression of the oncogenesis of EBV-infected gastric epithelial cells.